Pemicu Kerapuhan Finansial dan Ketidakamanan Finansial (Studi pada Kelompok Rumah Tangga) - Sri Mulyantini; Dewi Indriasih; Agung Yulianto (Jurnal Kajian Akuntansi, 2025)
The economic crisis has a significant impact on the financial condition of the community and households. The emergence of financial fragility, as a result of declining income, spikes in spending, the absence of emergency funds, preparedness funds or buffers. From the crisis, it teaches the importance of having good financial planning, in order to be more able to withstand economic shocks in the future. This study aims to study the factors that impact financial fragility, and see how it impacts financial insecurity. Survey data in this study will be analyzed using path analysis on the variables of financial insecurity, financial fragility, debt burden, healthcare investment and savings preparedness. The results show that debt burden is a factor that plays a fairly large role. In addition, financial fragility and healthcare investment affect the increase or decrease in financial insecurity. However, the savings preparedness variable does not have a significant effect on the increase or decrease in financial insecurity. The fundamental contribution of this study highlights the crisis that causes households to face financial difficulties and causes changes in lifestyle patterns and social challenges. This is mainly due to the absence of financial buffers, not investing in health and not providing sufficient preparedness funds.